2004
DOI: 10.1093/ptj/84.2.137
|View full text |Cite
|
Sign up to set email alerts
|

Leadership, Administration, Management, and Professionalism (LAMP) in Physical Therapy: A Delphi Study

Abstract: Background and Purpose. The knowledge and skills needed by physical therapists entering practice in the areas of leadership, administration, management, and professionalism (LAMP) are not known. Using the LAMP components identified by American Physical Therapy Association's Section on Administration, this study sought to define the range of LAMP content pertinent to physical therapy clinical management and to explore LAMP knowledge and skills required of physical therapists upon entry into the profession. Subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 9 publications
1
31
0
Order By: Relevance
“…Hybrid clinician managers have expert clinical knowledge, manage their professional colleagues, other health care professionals and organisational processes in their departments (Dopson et al, 2002;Fitzgerald and Dufour, 1998;Fitzgerald and Ferlie, 2000;Rees, 1996;Forbes and Prime, 1999;Lopopolo et al, 2004;Iedema et al, 2003). The challenge for clinical specialists is to manage dual professional roles within the organisational context (Allen, 1995).…”
Section: Hybrid Clinician Managersmentioning
confidence: 99%
“…Hybrid clinician managers have expert clinical knowledge, manage their professional colleagues, other health care professionals and organisational processes in their departments (Dopson et al, 2002;Fitzgerald and Dufour, 1998;Fitzgerald and Ferlie, 2000;Rees, 1996;Forbes and Prime, 1999;Lopopolo et al, 2004;Iedema et al, 2003). The challenge for clinical specialists is to manage dual professional roles within the organisational context (Allen, 1995).…”
Section: Hybrid Clinician Managersmentioning
confidence: 99%
“…A survey of physical therapy educators indicated that 98% of respondents considered professionalism an important component of the physical therapy curriculum (Davis, ). Educators advocated for the promotion of professional behaviors early in the education of doctoral students in physical therapy (Lopopolo et al, ; Johanson, ) to diminish lapses of professionalism such as tardiness and lack of personal responsibility (Davis, ).…”
Section: Introductionmentioning
confidence: 99%
“…In 2003, the American physical therapy association developed the core values definition and included it as part of credentials and requirements for entry-level PT programmes [8]. In 2004, the eleven ethical principles were established by American Physical Therapy Association (APTA) as the Guide for professional conduct that involved the core values necessary for professional autonomy and interprofessional care [9]. Understanding the current levels of professionalism not only provides a baseline information upon which to further develop using educational and professional development strategies, but also to facilitate enhanced professionalization by addressing individual-and professional-related factors.…”
Section: Introductionmentioning
confidence: 99%